Fusion oncogenes in rhabdomyosarcoma: model systems, mechanisms of tumorigenesis, and therapeutic implications - Sankhe, Chinmay S.; Hall, Lisa; Kendall, Genevieve C. (Frontiers in Oncology, 2025)
Rhabdomyosarcoma (RMS) contributes to 3% of all childhood cancers with roughly 400-500 cases diagnosed each year in the United States. The World Health Organization classifies rhabdomyosarcoma into four histological subtypes which include alveolar, embryonal, spindle-cell and pleomorphic. The primary genetic drivers in a subset of alveolar and spindle-cell histological subtypes are gene fusions. This review explores the fusion oncogenes identified in RMS such as PAX-and NCOA2-based fusions, along with discussing studies defining fusion oncogene biology and tumorigenic mechanisms. Focus areas include data around transformation events and progression along with dysregulated biological processes. Furthermore, we summarize model systems, ranging from cell to animal models, that have been implemented to study fusion oncogenes identified in RMS. With the constant identification of novel fusion oncogenes, this review also emphasizes the need for genetically characterizing RMS tumors and rapidly developing new model systems. These models are critical to study fusion oncogene activity and to delineate key regulatory players and potential therapeutic targets that suppress tumorigenesis. The identification of RMS fusion oncogenes and integration with animal and cell culture models will help identify conserved molecular targets, optimize therapeutic approaches, and ultimately improve clinical outcomes for children with RMS.